Challenges for Clinical Drug Development in Pulmonary Fibrosis - White, Eric S.; Thomas, Matthew; Stowasser, Susanne; Tetzlaff, Kay (Frontiers in Pharmacology, 2022)
Pulmonary fibrosis is a pathologic process associated with scarring of the lung interstitium. Interstitial lung diseases (ILDs) encompass a large and heterogenous group of disorders, a number of which are characterized by progressive pulmonary fibrosis that leads to respiratory failure and death. Idiopathic pulmonary fibrosis (IPF) has been described as an archetype of progressive fibrosing ILD, and the development of pirfenidone and nintedanib has been a major breakthrough in the treatment of patients with this deadly disease. Both drugs principally target scar-forming fibroblasts and have been shown to significantly slow down the accelerated decline of lung function by approximately 50%. In addition, nintedanib has been approved for patients with other progressive fibrosing ILDs and systemic sclerosis-associated ILD. However, there is still no cure for pulmonary fibrosis and no meaningful improvement of symptoms or quality of life has been shown. Advancement in research, such as the advent of single cell sequencing technology, has identified additional pathologic cell populations beyond the fibroblast which could be targeted for therapeutic purposes. The preclinical and clinical development of novel drug candidates is hampered by profound challenges such as a lack of sensitive clinical outcomes or suitable biomarkers that would provide an early indication of patient benefit. With the availability of these anti-fibrotic treatments, it has become even more difficult to demonstrate added efficacy, in particular in short-term clinical studies. Patient heterogeneity and the paucity of biomarkers of disease activity further complicate clinical development. It is conceivable that future treatment of pulmonary fibrosis will need to embrace more precision in treating the right patient at the right time, explore novel measures of efficacy, and likely combine treatment options.